2017
DOI: 10.17501/icedu.2017.3131
|View full text |Cite
|
Sign up to set email alerts
|

doi.org/10.17501/icedu.2017.3131 3rd International Conference on Education, 20-22 April 2017, Kuala Lumpur, Malaysia INTEGRATING ELEMENT OF GREEN SKILLS IN THE 21st CENTURY LEARNING

Abstract: Abstract:The outline of introducing green skills for a sustainable development is contained in the document called Transformation of Technical Vocational Education and Training (TVET), which is part of the 11th Malaysia Plan. There is a need to incorporate green skills into TVET programs to achieve sustainable development in the country, and in turn stimulate inclusive economic growth. The Ministry of Education, Malaysia launched the initiatives of the 21st century education in 2015. The secondary school stand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 12 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…Currently, environmental knowledge has been integrated into the curriculum to foster attention for the environment and develop green skills. [16][17] However, several studies have shown that the level of green skills remains low [18]. So, the aims of this literature review is to investigate the relationship between environmental awareness and green skills by analyzing relevant research conducted in this field.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, environmental knowledge has been integrated into the curriculum to foster attention for the environment and develop green skills. [16][17] However, several studies have shown that the level of green skills remains low [18]. So, the aims of this literature review is to investigate the relationship between environmental awareness and green skills by analyzing relevant research conducted in this field.…”
Section: Introductionmentioning
confidence: 99%